EXPLORATIVE ANALYSIS OF YOUTUBE CHANNEL OF ZAKAT INSTITUTION IN INDONESIA: A DOCUMENTATION STUDY OF NU CARE'S YOUTUBE CHANNEL - Furqonul Haq (AN NUQUD, 2023)
YouTube is one of the information media that is favored by many people today. Information related to the performance of zakat institutions in Indonesia can be obtained from the YouTube channel of the zakat institution, for example the NU Care YouTube channel. The purpose of the research is to qualitatively analyze the profile and columns on the NU Care YouTube channel. The research method is descriptive qualitative with an explorative approach. The results showed that the NU Care YouTube channel has a profile with 3.61K subscribers and 309 video posts. The NU Care YouTube channel has nine columns like most other YouTube channels. Of the nine columns, only eight columns (home, videos, shorts, live, community, channels, about and search) can be analyzed exploratively. While the playlists column cannot be analyzed exploratively